On The Issue Of Some Toponyms From Samurzakano - Lomaia, Shorena (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Subject matter of the article is certain toponyms which can’t be found in large monograph: “Geographical names of Samurzakano”. Jali. The village situates in Ochamchire community, among the villages of Mokvi, akvaska and Gufi. The etymology of the village name isn’t studied scientifically, as for the folk etymologies they are the following: 1) This territory used to abound with finest tree species (mainly box trees), which were sold to Turkey. That’s why the initial name of this place is Ojalon (compare Ojalefe, Ojale - a forest) [Kipshidze, 1994]. nja//mja//ja Laz. copmare dzeli. Mengrelian ja [Chikobava, 1938]. Georgian dzel-dzel-I “tree”; Mengrelian ja-ja “tree”; jal-ef-I “trees; o-jal-e-shi “dzelisa”; Sadzelisi (grape breed), che-ja “poplar”; (in ex white tree); Laz. ja/-nja-/mja/ja-/nja-/mja “tree” Laz dialect also confirms jailoni/jalona [Tandilava, 2013]. Jaloni - forest zone of a mountain from Lakadi to Sheheleti (mount), ja (Mengrelian) “tree”: - jaloni forest [Tskhadaia, 2013] . According to different version, there was a village at that place, inhabitants of which had become the victims of certain misfortune, only one man had survived, Jali by name, who didn’t abandon home, got married and lived his life there. It’s interesting part that the village is divided into two parts: Margalepish Jali, e.g. Jalagrua “Mengrelian jali” and Apkhazebish Jali, e.g. Jalapsua “Abkhazian Jali. Next to Jali there is the village Mokvi, which has different phonetic version Muku/Moku. The river has the same name: Mokvi/Mokvtskhari/Mokushtsyari. Several micro toponyms of this river are given according to personal names of people: Petresh Tomba, Koto, … Mokvi church situates nearby Mokvish Okhvame/Mokvi church. Interesting micro toponyms are Patritsakhu/Patratsaxu and Atidashu/Atashadu, (also Gupi, Mokvi), the structure-etymology of which are the subjects of different research.